Identification and validation of P4HB as a novel autophagy-related biomarker in diabetic nephropathy - Bai, Fang; Yu, Kuipeng; Yang, Yanjiang; Zhang, Yimeng; Ding, Lin; An, Xin; Feng, Feng; Sun, Nan; Fan, Jiahui; Liu, Lei; Yang, Huimin; Yang, Xiangdong (Frontiers in Genetics, 2022)
Diabetic nephropathy (DN), a frequent microvascular complication of diabetes, has been recognized as a primary cause of chronic kidney disease (CKD) and end-stage renal disease (ESRD). Previous studies found that autophagy of renal tubular epithelial cells plays an important role in DN pathogenesis. Our research aimed to investigate the differentially expressed autophagy-related genes (DEARGs) between DN and healthy renal tubule samples and identify a novel autophagy-related biomarker associated with tubulointerstitial injury in DN. In this study, gene expression profiles of renal tubules from 10 DN patients and 24 healthy controls in the GSE30122 dataset were analyzed, and 43 DEARGs were identified by bioinformatics analysis. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis and correlation analysis were performed on DEARGs, and hub gene prolyl 4-hydroxylase subunit beta (P4HB) was screened by protein–protein interaction, and verified by utilizing other datasets and stimulating HK-2 cells under high glucose concentration. We found that the expression of P4HB in renal tubules was correlated with renal function. In summary, our research provided novel insights for the comprehension of DN molecular mechanisms and identified P4HB as a novel autophagy-related biomarker of DN.